Obecność wymiaru eschatologicznego w doczesności. Punkt widzenia prawosławnego - PAPROCKI, Henryk (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
For the Orthodox Church, eschatology is not a separate treatise, rather, it gives direction to the entire theology, as well as points to the sense of the existence of a human being, whose end purpose is resurrection. Thus one can learn more about eschatology from liturgy, in particular from the Lenten and Paschal liturgies. There are two dimensions to eschatology: the personal one, concerning the death (destiny) of an individual human being and the universal one, namely, the second coming of Christ (the destiny of the world and of humanity at large). Since the Orthodox Church has not defined eschatology dogmatically, a range of its diverse interpretations is possible, from the extremely pessimistic ones (e.g. St. Augustine’s idea of massa damnata) to those announcing universal salvation and apocastasis (e.g. the thought of St. Gregory of Nyssa, or a certain current of Russian theology). The Christian East entrusts the fate of the dead to God’s mercy and to human prayer (as recommended by St. Isaac the Syrian among others), thus stressing that the last word belongs to hope. Translated by Dorota Chabrajska